ANALISIS MINAT BELAJAR SISWA KELAS VIII SMP NEGERI SOKORIA DALAM PEMBELAJARAN MATEMATIKA DIMASA PANDEMI COVID– 19 - Yuliana Monika Seti; Juwita Merdja; Ningsih Ningsih (Program Studi Pendidikan Matematika, 2022)
This study aims to determine the learning interest of students class VIII SMP Negeri Sokoria in learningmathematics during the covid-19 pandemic. This type of research is descriptive qualitative. Sources of data usedprimary and secondary. Procedures for collecting data by means of questionnaires and documentation.Researcher took students of class VIII-C SMP Negeri Sokoria, totaling 30 people as the subjet. Data analysis inthis study is descriptive with percentages presented in tabular form. The results of this study indicate that thepercentage of student interest in class VIII SMP Negeri Sokoria in learning mathematics during the covid-19pandemic is in the moderate category seen from the four indicators. The percentage of student interest in learningbased on the indicator of feeling happy to get a percentage of 65.33% with the medium category, the percentageof student interest in learning based on the indicator of interest getting a percentage of 64.40% with the mediumcategory, the percentage of student interest in learning based on the indicator of attention getting a percentageof 64.80% with the category medium, the percentage of student interest in learning based on indicators ofinvolvement obtained a percentage of 67.20% with the medium category.